2020
DOI: 10.1002/ajhb.23454
|View full text |Cite
|
Sign up to set email alerts
|

Proportionality indices, geographic altitude, and gestational age in newborns from Jujuy, Argentina

Abstract: Background There are several different proportionality indices (PRIs) to evaluate size at birth by gestational age (GA). Yet, the explanatory power of alternative PRIs has not been evaluated in highland (HL) populations. Aim Evaluate the relative utility of three PRIs, weight to length ratio (W/L), body mass index (BMI), and ponderal index (PI), for assessing nutritional status in newborns (NBs) from highland (HL ≥ 2000 m) and lowland (LL < 2000 m) regions of the Jujuy Province of Argentina. Subjects and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
0
8
0
4
Order By: Relevance
“…A pesar de la importancia de analizar la RCIU, debido a que los RN con esta condición presentan, en comparación con los RN con un crecimiento intrauterino normal, un mayor riesgo de sufrir consecuencias adversas en la primera infancia y la niñez en términos de mortalidad, morbilidad, crecimiento, como así también de obesidad, hipertensión, diabetes, enfermedades c a r d í a c s y p u l m o n a r e s , y a c c i d e n t e s cerebrovasculares en la vida adulta, 23,24 existen pocos antecedentes sobre la evaluación de PEG con el estándar INTERGROWTH-21st. 4,7,9,22 En este estudio, se encontró una prevalencia de PEG del 7 % (P10) y el 2,3 % (P3) en Jujuy para todo el período analizado. Para el año 2010, en un estudio global de este indicador, la prevalencia de PEG (<P10) para Latinoamérica y el Caribe (12,5 %; IC 9,4-16,3) y Argentina (11,3 %; IC 8,2-15) fue superior a lo hallado en este trabajo, tanto a nivel provincial como regional.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A pesar de la importancia de analizar la RCIU, debido a que los RN con esta condición presentan, en comparación con los RN con un crecimiento intrauterino normal, un mayor riesgo de sufrir consecuencias adversas en la primera infancia y la niñez en términos de mortalidad, morbilidad, crecimiento, como así también de obesidad, hipertensión, diabetes, enfermedades c a r d í a c s y p u l m o n a r e s , y a c c i d e n t e s cerebrovasculares en la vida adulta, 23,24 existen pocos antecedentes sobre la evaluación de PEG con el estándar INTERGROWTH-21st. 4,7,9,22 En este estudio, se encontró una prevalencia de PEG del 7 % (P10) y el 2,3 % (P3) en Jujuy para todo el período analizado. Para el año 2010, en un estudio global de este indicador, la prevalencia de PEG (<P10) para Latinoamérica y el Caribe (12,5 %; IC 9,4-16,3) y Argentina (11,3 %; IC 8,2-15) fue superior a lo hallado en este trabajo, tanto a nivel provincial como regional.…”
Section: Discussionunclassified
“…En Argentina, la mayoría de los antecedentes pertenecen a la provincia de Jujuy, debido a su localización sobre las estribaciones andinas, con ecorregiones situadas sobre un gradiente altitudinal (Puna ≈3000 msnm; Quebrada ≈2000 msnm; Valle ≈1000 msnm y Ramal ≈500 msnm) y con características demográficas, socioeconómicas y culturales propias. 12,[19][20][21][22] Teniendo en cuenta las características topográficas antes mencionadas de la provincia de Jujuy y disponiendo de un registro continuo de los nacimientos de aproximadamente 25 años, el objetivo de este trabajo fue analizar la distribución espacial de las prevalencias de PEG y su tendencia secular .…”
Section: Introductionunclassified
“…Maternal height, pregestational maternal weight, and weight increase during pregnancy have been identified as the main maternal capital components [ 5 ] which determine fetal growth patterns and, consequently, the size of newborns [ 35 ]. Previous studies in Jujuy have shown that maternal weight, height, and BMI were positively correlated to equivalent newborn variables, and that all these anthropometric variables were inversely correlated to altitude [ 36 ]. The close relationship between maternal anthropometry and fetal size, evaluated with SGA and LGA newborns, is made evident by the variation in prevalence of these indicators, showing that there is a clinically significant difference in birth weight percentiles when they are stratified by maternal height and weight [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the prevalence of SGA and LGA newborns according to type of surname (indigenous or foreign) in Jujuy populations are probably related to ethnic variations, altitude, and maternal BMI. Jujuy populations with indigenous surnames, particularly populations in the highlands, have lower average weights and heights, lower BMIs, and are less mixed ethnically than populations in the lowlands [ 10 , 11 , 12 , 13 , 14 , 15 , 36 ]. Risk factors found in the bivariate analysis between AGA and LGA are probably related to maternal BMI, the only risk factor for LGA that GLM tion returns.…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic (7,8) , environmental factors (9,10) , socioeconomic inequality (7,10,11) , and parasitic infectious diseases (12) have been associated with malnutrition in children under five years old. It is widely acknowledged that environmental factors (e.g., geographical factors) are crucial to defining the human growth pattern characterized by anthropometric and function features (e.g., birth length, birth weight), and children located in different resident altitudes also exhibited significant heterogeneity in growth patterns (9,13) . Several studies conducted in Ethiopia (14) , Tibet (15) , and Ecuador (16) revealed the negative or positive influence of geographical altitude on nutritional outcomes.…”
Section: Introductionmentioning
confidence: 99%